2016
DOI: 10.1039/c5cp06702b
|View full text |Cite
|
Sign up to set email alerts
|

Towards physical interpretation of substituent effects: the case of meta- and para-substituted anilines

Abstract: Quantum chemical modeling was used to investigate the electron-donating properties of the amino group in a series of meta- and para-X-substituted anilines (X = NMe2, NH2, OH, OMe, CH3, H, F, Cl, CF3, CN, CHO, COMe, CONH2, COOH, NO2, and NO). Different methods (HF, B3LYP, and M06-2X) and basis sets (6-31+G(d,p), 6-311++G(d,p), and aug-cc-pVDZ) were applied and compared with the MP2 approach. The B3LYP/6-311++G(d,p) method was chosen as the most appropriate one. The substituent properties were described by σ, cS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 57 publications
0
76
1
Order By: Relevance
“…Moreover, the cSAR approach can be applied to both, the varying substituents, [as cSAR(X)], as well as to the reaction site (or a fixed functional group in the series X-R-Y), [cSAR(Y)], and allows to estimate the regression line cSAR(Y) vs. cSAR(X). The slope of this regression describes the strength of interactions between X and Y [9,10]. It was also shown that changes in geometry of the components of the functional group Y correlate well with cSAR(Y) [12] and hence correlate also with cSAR(X) that was documented for aniline [10], nitrobenzene [13], and benzoic acid [14] substituted derivatives.…”
Section: ) Is Alwaysmentioning
confidence: 83%
See 2 more Smart Citations
“…Moreover, the cSAR approach can be applied to both, the varying substituents, [as cSAR(X)], as well as to the reaction site (or a fixed functional group in the series X-R-Y), [cSAR(Y)], and allows to estimate the regression line cSAR(Y) vs. cSAR(X). The slope of this regression describes the strength of interactions between X and Y [9,10]. It was also shown that changes in geometry of the components of the functional group Y correlate well with cSAR(Y) [12] and hence correlate also with cSAR(X) that was documented for aniline [10], nitrobenzene [13], and benzoic acid [14] substituted derivatives.…”
Section: ) Is Alwaysmentioning
confidence: 83%
“…This approach allows to determine, in an energetic scale, the nature of the interaction between substituents in disubstituted systems. It was documented that the SESE characteristic correlates well with classical substituent constants [9,10]. SESE is a descriptor of substituent electron donating/attracting properties and takes into account all interactions in the X-R-Y system.…”
Section: ) Is Alwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…cSAR(X) is a sum of atomic charges of X and of the ipso atom (carbon or nitrogen in our case) to which the substituent is attached. It was shown that cSAR(X) values correlate well [15,[19][20][21][22] with the Hammett substituent constants [13]. Moreover, it was documented that cSAR of a functional group (NO and NMe 2 ) in para-substitute d d e r i v a t i v e s o f n i t r o s o b e n z e n e a n d N , Ndimethylaminebenzene nicely describes changes in the geometry in these groups [23].…”
Section: Introductionmentioning
confidence: 90%
“…The use of the idea of cSAR(X) enables a deeper look at the substituent effects [44,45]. The application of this concept makes the comparison of group characteristics available and easier to …”
Section: Consequences Of the Nitro Group Rotation In P-nitroanilinementioning
confidence: 99%